A Reflection on University Teaching Practice from the Perspective of Discursive Strategies - Edgardo Ruiz Carrillo (Universidad Autónoma de Baja California, 2013)
This paper aims to promote teacher reflection on the use of discursive strategies. Four biology professors participated in the study; content analysis was used to categorize each professor's reflection on his or her teaching practice. First, we found it necessary for the four teachers to understand the student's learning-related interests as well as the intention of self-recognition and the monitoring of their own practice. Secondly, we found that the reflection of three of the four professors concerned the contextual deficiencies of the classroom, their questioning of the instrument in relation to their practice and, lastly, their self-justification for not using some strategies, promoting discursive changes in their teaching practice.